MEDIASI WORK ENGAGEMENT PADA PERCEIVED ORGANIZATIONAL SUPPORT YANG DIRASAKAN TERHADAP JOB SATISFACTION DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - nala tri kusuma; ignatius soni kurniawan; jajuk herawati (Universitas Lancang Kuning, 2021)
The purpose of this research is to analyze whether work engagement mediates perceived organizational support toward job satisfaction and organizational citizenship of SMEs in Yogyakarta. The sampling method of this research used accidental sampling by spreading questionnaire. Total of the sample were 100 respondents. The result showed that the relationship between perceived organizational support and job satisfaction was partially mediated by work engagement. Furthermore, this research also proved that work engagement partially has not mediated the relationship between perceived organizational support and organizational citizenship behavior. Implications of the findings suggest strengthening perceived organizational support and work engagement consistently in increasing organizational citizenship behavior in the organization